Jewish Rewritten Scripture and Greco-Roman Imitation: Two Sides of the Same Coin? - Bowes, William B. (Journal of ancient Judaism, 2026)
The corpus of texts called "Rewritten Scripture" have long been subject to debate about their categorization. When differentiating between minimalist (form-oriented) and maximalist (process-oriented) schools of thought, distinctions must be made between elements like content, techniques, purpose, and function to determine where these texts belong. This article does not attempt to redefine or reclassify Rewritten Scripture as a phenomenon, but contends with arguments suggesting that Rewritten Scripture is basically equivalent to Greco-Roman imitation (μίμησις/imitatio). While imitation has its own categorization problems, I argue that Rewritten Scripture can be meaningfully distinguished from μίμησις/imitatio. Even with some overlaps, if we imagine a continuum of source reuse, these are at different points. I argue this with reference to 1) function, 2) limits, 3) writer, and 4) authority of source material. Both have different types of rewriting, resulting in distinguishable types of texts. There is something distinctive about the Jewish texts called Rewritten Scripture.